Human Resource Management in Islamic Business: Employee Education and Competency Development Perspective - Permatasari, Retno Japanis (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to explore human resource management in sharia business with a focus on the perspective of employee education and competency development. The research method used is qualitative with a descriptive-analytical approach. Data were collected through in-depth interviews, participant observation, and literature studies from reliable sources. In the context of sharia business, human resource management has unique characteristics that are based on Islamic values, such as justice, transparency, and social responsibility. Employee education and competency development are crucial aspects in supporting the implementation of these values. The results of the study indicate that a sharia-based approach can significantly improve employee performance, especially in terms of work ethics, productivity, and their involvement in achieving organizational goals. Training oriented towards Islamic values, such as integrity and noble morals, is considered effective in creating a harmonious work culture. In addition, an experiential learning model is applied to improve employees' technical and non-technical skills. This study concludes that education and competency development strategies that are in accordance with sharia principles can provide a positive contribution to the sustainability of sharia business while supporting employee welfare holistically. These findings provide recommendations to human resource managers in Islamic businesses to integrate Islamic value-based education programs and ongoing training as part of their management strategy